IMPLIKASI HUKUM DAN KEBIJAKAN TERHADAP KASUS KERACUNAN MAKANAN DALAM PROGRAM MAKANAN BERGIZI GRATIS DI INDONESIA - Imanuel Inriyanto Ruslak Hammar; Siria Silubun; Roberth Kurniawan Ruslak Hammar (PATRIOT, 2025)
The Free Nutritious Food Program is an affirmative state policy aimed at improving the fulfillment of children's rights to adequate health and nutrition. However, in practice, this program has created serious problems, particularly related to food poisoning incidents in schools, reflecting weak oversight and law enforcement in the area of ​​food safety. This study aims to analyze the legal accountability of the state and local governments for food poisoning cases within the Free Nutritious Food Program, assess the adequacy of the national regulatory framework related to food safety and consumer protection, and examine the implications of public policy for protecting children's rights to health. The research method used is a normative juridical approach with a statutory and conceptual approach, through a literature review of primary, secondary, and tertiary legal materials. The results indicate that legal accountability for food poisoning incidents can be imposed through administrative, civil, and criminal proceedings, depending on the level of negligence and the resulting impact. Normatively, regulations in the area of ​​food safety and consumer protection are adequate, but their implementation still faces serious obstacles in the form of weak oversight, limited institutional capacity, and a lack of ongoing evaluation mechanisms. Therefore, the free nutritious food policy requires strengthening the integrated monitoring system, implementing the precautionary principle, and increasing state accountability to ensure maximum protection of children's rights to safe and nutritious food